Globalization, Utopia and Postcolonial Science Fiction - Smith, E. author. aut Link
VIII, 244 p.
Keywords: This study considers the recent surge of science fiction narratives from the postcolonial Third World as a utopian response to the spatial, political, and representational dilemmas that attend globalization.